A pilot case-control study on the association between N-acetyl derivatives in serum and first-episode schizophrenia. (February 2019) - Huang, Ninghua; Cao, Bing; Brietzke, Elisa; Park, Caroline; Cha, Danielle; Pan, Zihang; Zhu, Judy; Liu, Yaqiong; Xie, Qing; Zeng, Jing; McIntyre, Roger S.; Wang, Jingyu; et al.
Highlights: Based on the HILIC LC-MS platform, our pilot study analyzed the association between the levels of five N -acetyl derivatives and schizophrenia. Higher levels of N -acetyl-glutamine were found in first-episode patients with schizophrenia compared to HC in our study. Decreased N 6 -acetyl- L -lysine in first-episode patients with schizophrenia were found compared to HC. The findings may prove useful in identifying novel disease markers and/or drug target molecules in schizophrenia. Abstract: N- acetyl group metabolites are a general class of endogenous compounds characterized by a conjugated system consisting of an acetyl group and nitrogen moiety. The aim of our exploratory pilot case-control study is to compare the levels of five N- acetyl derivatives (i.e., N- acetyl-glutamine, N- acetyl-ornithine, N 6 -acetyl- L -lysine, N- acetyl-putrescine, and N- acetyl-galactosamine) in serum samples between individuals with first-episode schizophrenia and healthy controls (HC). A 1:2 age- and sex- matched pilot case-control study was performed, involving 30 cases of first-episode schizophrenia and 60 HC aged between 18 and 40 years old. The serum samples containing these N- acetyl derivatives from (first-episode patients with schizophrenia and HC were measured using liquid chromatography-tandem mass spectrometry (LC-MS). Results indicated that higher levels of N- acetyl-glutamine and lower levels of N 6 -acetyl- L -lysine may have a significant association with schizophrenia after adjusting for age, sex and BMI. N- acetyl-putrescine was elevated among subjects with first-episode schizophrenia when compared to HC, suggesting it as a predictor for schizophrenia onset. Further exploration of the mechanisms of N- acetyl group metabolites with respect to schizophrenia is warranted and may be useful for identifying novel disease markers and/or drug target molecules in schizophrenia.